Rice straw washwater with urea and co-digestion of anaerobic treatment application - Rosli, Nurul Shafiqah (2018)
Rice straw is a sustainable warranted biomass resource for the production of renewable energy through combustion; and rice straw washing is a simple method to improve the thermal behaviour of straw prior to combustion. Nonetheless, the environmental issue will arise with regards to the produced rice straw washwater (RSWW) if it left untreated, due to the presence of considerable amount of organic matter and leached alkali metals cations primarily potassium. The application of anaerobic biodegradation not only can treat the RSWW but also produce the methane as a fuel. This liquid type substrate is suitable for upflow anaerobic sludge blanket reactor (UASB), where a clear effluent can be produced. This study was conducted in a continuous mode of hydraulic retention time (HRT) 24 hours at mesophilic temperature of 37±2℃. Results indicate the potential of RSWW in generating biogas at organic loading rate (OLR) of 1.0 g COD/L/day, with the stabilized specific methane production (SMP) of 0.16 to 0.18 L CH4/g CODrem and COD removal between 81% and 83%. However, SMP drop to the lowest production at 0.09 L CH4/g CODrem as OLR was further increased to 2 g COD/L/day. Continuous accumulation of potassium (K) in the digester, up to 8.0 mg K per gram sludge inoculum correspond to the rapid drop in COD removal along with SMP. The accumulation of K was confirmed and proven by scanning electron microscope (SEM) together with EDX analysis on the inoculum. Addition of 3% urea into RSWW at high OLR enhance the production of methane with the highest average value of 0.21 L CH4/g CODrem, with the increment by 90.9% compared to RSWW without urea. Meanwhile, during the co-digestion of RSWW and domestic wastewater (DW), the maximum SMP and COD removal were recorded at 0.30 L CH4/g CODrem and 92.2% respectively, at mixing ratio of 3:7 (RSWW:DW), corresponded to 30.4 C:N ratio. The maintain of TAN below 200 mg/L, pH between 6.5 and 7.0 and IA/PA under 0.3 suggests that the co-digestion of RSWW with DW provide a better stability and higher buffering capacity at high organic loading system without adversely affect the reactor performances. Continuous stir tank reactor (CSTR) showed a slightly better performance in mono anaerobic digestion of RSWW for both COD removal and SMP by 5.1% and 36.4% higher compared to UASB reactor. Nevertheless, the energy balance calculation demonstrated that the net energy output from UASB was 44.4% higher than in CSTR, at 0.26 kWh/kg. This study implies that the RSWW can be used as a source for renewable energy production and further enhanced by the addition of urea as an external source of nitrogen. Meanwhile, co-digestion is proven to significantly improve the yield of methane along with the removal of organic matter.